S27 The effects of statin therapy on inflammatory markers in patients with copd: a double blind randomised controlled trial. (14th November 2013) - John, M; Knox, AJ; McKeever, TM; Meakin, G; Bailey, H; Cockcroft, JR; Shale, DJ; Harrison, TW; Bolton, CE
Abstract : Background: Systemic and airway inflammation are recognised in COPDand reducing inflammation has been postulated to alter disease course 1 . Statins have pleiotropic effects including anti-inflammatory properties 2 . A study in asthma showed that statins reduced sputum macrophage levels 3 . We hypothesised that statins would reduce systemic (hs-CRP) and airway (exhaled nitric oxide: FeNO, sputum neutrophils and macrophages) inflammation in patients with COPD. Methods: Clinically stable patients with confirmed COPD were recruited and randomised to either simvastatin 20mg od (active) or placebo for 6 weeks in a double blinded parallel group randomised controlled trial. Circulating hs-CRP and fasting lipids were measured in all subjects' pre- and post- treatment. 5-flow FeNO and induced sputum were performed in consenting patients where possible pre- and post-treatment. Primary analysis compared the six week change in each inflammatory marker between active and placebo groups. Results: Patients were matched for age, sex, smoking and lung function; active: n = 33, placebo: n = 37. Compliance was good and the active group achieved total cholesterol reduction: between arms mean (95% CI): -1.1 (-1.3, -0.8)mmol/L, p < 0.001. Baseline median (IQR) hs-CRP was 3.09 (1.3–7.4)mg/l but there was no significant change after treatment between active and placebo: between arms mean (95% CI) 0.5(-3.2, 4.1)mg/l. Baseline sputum samples were obtained in n = 27 and 22/27 had neutrophilic sputum. Paired samples were obtained in 20 patients: active n = 8 and placebo n = 12 with no significant difference in change between treatment arms for sputum neutrophils or macrophages. FeNO was measured in 36 patients: active n = 17, placebo n = 19 with no significant difference in change between arms. Conclusions: In this pilot RCT, despite significant lipid lowering, there was no demonstrable systemic or airway anti-inflammatory effect over 6 weeks with simvastatin 20mg od in patients with COPD. Baseline results showed a majority had neutrophilic sputum however only a small proportion had airway inflammation evaluation. Trial reference: NCT01151306 Supported by NIHR RfPB grant References: Sin, DD, et al . AJRCCM 2004;170:760–765 Walsh, G. M Expert Review of Respiratory Medicine 2008;2(3):329–335 Hothersall, EJ, et al., Thorax 2008;63(12):1070–5